Mitochondrial genomes advance phylogenetic hypotheses for Tylenchina (Nematoda: Chromadorea). (6th April 2015) - Kim, Jiyeon; Lee, Sang‐Hwa; Gazi, Mohiuddin; Kim, Taeho; Jung, Daewui; Chun, Jae‐Yong; Kim, Sanghee; Seo, Tae‐Kun; Park, Chungoo; Baldwin, James G.; Nadler, Steven A.; Park, Joong‐Ki
<x xml:space="preserve">Abstract</x> Within the nematode class Chromadorea, the suborder Tylenchina is an ecologically and morphologically diverse assemblage of nematodes that includes free‐living microbivores, fungivores and various types of plant parasites. A recent nematode classification system based largely on SSU rDNA phylogenetic trees classified suborder Tylenchina to include four infraorders: Panagrolaimomorpha, Cephalobomorpha, Tylenchomorpha and Drilonematomorpha, and phylogenetic relationships among species of these infraorders have not always been robustly supported. In this study, we determined the complete mitochondrial genome sequences of three Tylenchina species (Aphelenchus avenae [Aphelenchidae, Tylenchomorpha], Halicephalobus gingivalis, Panagrellus redivivus [Panagrolaimomorpha]) and the partial genome sequence of Acrobeles complexus (Cephalobomorpha) and used these sequences to infer phylogenetic relationships among representatives of the Tylenchina and other nematodes. Phylogenetic analysis of amino acid sequences for 12 protein‐coding genes of 100 nematode species supports monophyly of: Chromadorea, Spiruromorpha, Oxyuridomorpha, Ascarididae + Toxocaridae + Anisakidae, Meloidogynidae + Pratylenchidae + Heteroderidae and Aphelenchoidea. Bayesian and maximum‐likelihood analyses also show the nested position of Diplogasteromorpha within Rhabditomorpha, and Rhigonematomorpha within Ascaridomorpha. These analyses also show non‐monophyly of: clade III, Ancylostomatidae, Panagrolaimomorpha, Tylenchina and Tylenchomorpha. Reconstructed mitochondrial genome phylogeny also revealed that among two main Tylenchomorpha groups, the monophyletic group representing Aphelenchoidea species was sister to the large clade consisting of Ascaridomorpha, Diplogasteromorpha, Rhabditomorpha and Rhigonematomorpha and some Panagrolaimomorpha species, whereas Tylenchoidea species were sister to the most inclusive assemblage containing all infraordinal groups of Chromadorea, except for P. redivivus (Panagrolaimomorpha) and Acrobeles complexus (Cephalobomorpha). The monophyly of Aphelenchoidea (i.e. sister relationship between Aphelenchidae and Aphelenchoididae) recovered in this study indicates that similarity in certain aspects of pharyngeal structure between these two families appears best explained by common ancestry, rather than convergent evolution.